Synthesis of Tapioca Starch/Palm oil Encapsulated Urea-Impregnated Peppercorn Biochar Controlled-Release Fertilizer for Soil Amendment - Daniel Hong Heng, Sim (University of Malaysia, Sarawak, 2024)
The slow-release property of biochar-based fertilizer is still facing limitation and it can be overcome by integrating encapsulating technology and biochar-based fertilizer. Starch has been introduced as an encapsulating material due to its low-cost and biodegradable nature, but the slow-release property is limited by its hydrophilicity. Hence, this study aimed to formulate the tapioca starch/PO encapsulated urea-impregnated peppercorn waste derived biochar controlled-fertilizer pellet (EUIB pellet), followed by investigation of the effect of EUIB pellet on the nitrogen release rate and kinetic, nitrogen leaching, water retention and okra plant growth. The CCD was utilized to investigate the effect of pyrolysis temperature, residence time and urea:biochar ratio on the nitrogen content. The optimum condition to synthesize urea-impregnated peppercorn derived biochar-based fertilizer powder (UIB powder) was 400 °C pyrolysis temperature, 120 minutes residence time and 0.6 urea:biochar ratio which resulted in a nitrogen content of 16.07%. The acidic surface functional groups and hydrophilicity decreased with increasing pyrolysis temperature. In contrast, the changes of acidic surface functional group and hydrophilicity were insignificant when residence time increased. The biofilm formulated using 8g of tapioca starch and 0.12 µL showed the lowest water absorption ability and was employed to encapsulate the urea impregnated biochar-based. The EUIB pellet had the greater crushing strength than urea-impregnated peppercorn derived biochar-based fertilizer pellet (UIB pellet). The UIB and EUIB pellets achieved complete nitrogen release after 90 minutes and 330 minutes, respectively. The Korsmeyer-Peppas model best described the nitrogen release mechanism of UIB and EUIB pellets. The enhancement of water retention ratio of UIB and EUIB pellets were more significant in the sandy textural soil than clayey-textural soil. The nitrogen content of pure urea and UIB pellet was completely leached from the sand after two and three leaching activities while the nitrogen of EUIB pellet was completely leached from the sand after five leaching activities. The EUIB pellet has enhanced the shoot length, root length, number of leaves, area of leaves, wet weight and dry weight of the okra plant as compared to UIB pellet, pure urea and control experiment. In conclusion, the EUIB pellet formulated in this study has the potential to be utilized as a slow/controlled-release fertilizer for soil amendment.